Phillip Ray Callaway, Extending the Torah: The Temple Scroll in Modern Research (Qumranica Mogilanensia 19; Kraków-Mogilany: The Enigma Press: 2022) - Tronina, Antoni (The Biblical Annals, 2022)
Book Review: Phillip Ray Callaway, Extending the Torah: The Temple Scroll in Modern Research (Qumranica Mogilanensia 19; Kraków-Mogilany: The Enigma Press: 2022).